Body fat depots and body condition score relationship: a comparison of two Spanish sheep breeds (Churra vs Merina) - Frutos P.; Mantecón A.R.; Revesado P.R.; González J.S. (Body condition of sheep and goats: Methodological aspects and applications, 1995)
Knowledge of the body fat depots is of central importance in extensive sheep production systems. The Body Condition Score (BCS) method has often been used as an index of nutritive status of the animals. Nevertheless, it must be considered that this is a subjective technique that was developed working with British sheep meat production genotypes, and variations in fat depots distribution have been reported when different genotypes are compared. To compare body fat depots and Body Condition Score relationship in two Spanish sheep breeds, 15 Churra mature ewes and 9 Merina ones were used. All animals were slaughtered and internal fat depots (channel and kidney, omental and mesenteric) removed and weighted. Chemical carcass and non-carcass fat were estimated in laboratory. The results of this work showed that BCS and body fat depots relationship was not different for both breeds. Churra ewes present a higher proportion of total internal fat in the empty body weight than Merina ones and a different internal fat depots distribution.
Seminar of the Working Group on Body Condition of Sheep and Goats of the FAO/CIHEAM Network on Sheep and Goats, 24-31 Mar 1994, Zaragoza (Spain)